Analysis of Cheerful Gymnastics Activities in Developing the Gross Motor Skills of Early Childhood at Al Fitrah Kindergarten, Jambi - Ratumas Sinta Naila (The Future of Education Journal, 2026)
Physical-motor ability is a developmental aspect that requires stimulation from an early age. One initiative undertaken by TK Al Fitrah Jambi is the implementation of "cheerful gymnastics" (senam ceria) activities. This study aims to analyze the planning, implementation, and impact on physical-motor development, as well as the supporting and inhibiting factors associated with these activities. A qualitative, descriptive research approach was employed. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model. The results indicate that the cheerful gymnastics activities were planned and executed systematically, comprising warm-up, core movement, and cool-down phases. These activities contributed positively to the children's physical-motor development, particularly regarding movement coordination, balance, agility, and self-confidence. Successful implementation was supported by teacher competence, available facilities and infrastructure, and the children's enthusiasm, while challenges included weather conditions, space limitations, and variations in the children's motor abilities. Thus, cheerful gymnastics serves as an effective alternative learning method for developing the physical-motor skills of early childhood learners.